Does oil palm certification create trade-offs between environment and development in Indonesia? - Lee, Janice Ser Huay (2021)
Environmental and social problems triggered by rapid palm oil expansion in the tropics have spurred the proliferation of sustainability certification systems such as the Roundtable on Sustainable Palm Oil (RSPO). While the RSPO aims to improve the impact of oil palm production on people and environments, its effect on local development, environmental quality, and, especially, potential trade-offs between these outcomes remain unclear. Here, we evaluate whether RSPO certification of large-scale industrial concessions has promoted village development and supported environmental quality in Indonesia, the top global palm oil producer. Using a panel dataset with observations from 11 000 villages in Kalimantan and Sumatra from 2003 to 2014, we apply rigorous quasi-experimental methods to quantify the RSPO's impacts on village development and environmental outcomes. In the short-run, RSPO contributed to environmental conservation, but had limited development outcomes. On average, relative to villages with non-certified concessions, RSPO certification reduced deforestation and protected primary forests in Sumatra and lowered the incidence of village-reported land pollution in Kalimantan. RSPO certification also increased the number of private educational facilities in Kalimantan, but had no statistically significant impacts on other development indicators. However, the trade-offs and complementarities between conservation and development vary by slope, a proxy for ecosystem fragility and oil palm profitability. On gentler slopes, we generally find complementarities between conservation and development outcomes. In Kalimantan, certification increased the number of private educational facilities and reduced deforestation and the incidence of land pollution on slopes < 2°. In Sumatra, certification retained more primary forests, decreased deforestation and the incidence of water pollution on slopes < 1°, along with a decrease in population density. Higher slopes in both locations were associated with environment and development trade-offs. We highlight the need to better understand the mechanisms behind the impacts of RSPO and emphasized how the outcomes of certification depend on the communities' bargaining power and the profitability of the land for oil palm production. Thus, we provide insights into understanding these mechanisms behind the impacts of RSPO, which is a prerequisite for improving the design of certification systems and their impacts on the ground.